METODE PENGASUHAN ANAK DALAM AL- METODE PENGASUHAN ANAK DALAM AL-QUR’AN: Telaah Tafsir Maqasidi - Rochma, Nur; Rohti, Wiwin Ainis; Mahmud, Amir; Kuswoyo, Nyoko Adi; Lukman, Lukman (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The purpose of this research is to find out child care methods and apply them to parents' daily care in caring for children and identify the application of maqasidi interpretations of Al-Qur'an verses in child care. This research uses a type of library research, and the study is presented descriptively and analytically. The result of the discussion is that the verses used in this parenting method include QS. An-Nahl verse 90, QS. Al-Baqarah verse 83, QS. Lukman verses 12-19, QS. An-Nur verse 58, QS. Ar-Rum verse 21, QS. An-Tin verse 4, QS. An-Nahl verse 78. This research focuses on verses on child rearing methods through a maqasidi interpretation approach. According to the maqasidi interpretation approach, the verses that describe the verse contain aspects of maqasidi including hifz al-din (guarding religion), hifz al-nafs (guarding the soul), hifz al-'aql (guarding reason), hifz al-nasl ( guarding offspring), and hifz al-mal (guarding property) and hifd al-daulah (guarding the state).